Treatment approach for elderly and unfit patients with chronic lymphocytic leukemia. Issue 12 (2nd December 2017) - Innocenti, Idanna; Autore, Francesco; Pasquale, Raffaella; Morelli, Francesca; Efremov, Dimitar G; Laurenti, Luca
ABSTRACT: Introduction : Elderly patients with chronic lymphocytic leukemia (CLL) or patients with comorbidities are often treated with chlorambucil (Chl) as front-line therapy despite relatively low response rates. The addition of a monoclonal anti-CD20 antibody to Chl substantially increases response rates and prolongs progression-free survival (PFS) in these patients, without increasing toxicity. As a result, the ESMO guidelines recommend that previously untreated CLL patients with relevant co-morbidity, but without TP53 deletion/mutation, should be treated with the combination of Chl plus an anti-CD20 antibody (rituximab, ofatumumab or obinutuzumab). Areas covered : This review focuses on the treatment approach of elderly and unfit patients with untreated chronic lymphocytic leukemia. Expert commentary : The addition of a monoclonal anti-CD20 antibody to Chl is currently the suggested treatment in this subset of CLL patients. The choice of the anti-CD20 antibody remains an open question, although obinutuzumab was found to be superior to rituximab, in a head-to-head comparison of Chl-based combinations, in untreated CLL patients with comorbidities, with higher progression free survival, complete remission rates and minimal residual disease-negative remissions. Because patients with a TP53 deletion/mutation are resistant to chemo-immunotherapy, treatment with the BTK inhibitor ibrutinib is recommended in this setting.